Boekbespreking (OverHolland, 2013)
Jaap Evert Abrahamse en Jan van DoesburgJerzy Gawronski (red.)Amsterdam Ceramics. A city’s history and an archaeological ceramics catalogue 1175-2011 Amsterdam (Bas Lubberhuizen) 2012, 336 pp.P.J. KnegtmansAmsterdam. Een geschiedenisAmsterdam (SUN) 2011, 440 pp. Peter Jan KnegtmansAmsterdam: een geschiedenis(‘Amsterdam: a history’)Amsterdam, SUN, 2011, 44